Molybdenum incorporated Cu1.69ZnSnS4 kesterite photovoltaic devices with bilayer microstructure and tunable optical-electronic properties. (December 2019) - Zhuk, Siarhei; Wong, Terence Kin Shun; Hadke, Shreyash Sudhakar; Lie, Stener; Guchhait, Asim; Gao, Yu; Wong, Lydia Helena; Cheng, Shuying; Wang, Xinghui; Dalapati, Goutam Kumar
Graphical abstract: Highlights: Mo incorporated CZTS with no secondary phases deposited by magnetron co-sputtering. Formation of bilayer CZTS absorber with different grain microstructure and porosity. Mo enhances P -type conductivity and absorbance of CZTS for wavelengths <600 nm. Voc deficit, Jsc, and FF improved for CZTS/CdS devices with optimized Mo content. PCE of optimized Mo incorporated CZTS solar cell increased to 5.49% from 1.63% Abstract: Molybdenum (Mo) incorporated Cu1.69 ZnSnS4 (CZTS) absorber has been deposited onto Mo-coated soda lime glass (SLG) by co-sputtering of Mo and non-stoichiometric quaternary compound targets. After sulfurization at 600 °C, Mo incorporation into CZTS was confirmed by X-ray diffraction (XRD) and secondary ion mass spectrometry (SIMS). From the observed shifts for the (1 1 2) and (2 2 0) peaks, both lattice parameters a and c of the CZTS unit cell were found to decrease with increasing Mo incorporation suggesting cationic substitution by Mo. The Mo incorporated CZTS has a bilayer microstructure in which the lower sub-layer adjacent to the substrate has a smaller grain size and higher porosity than the upper sub-layer. The lower sub-layer is also richer in Mo and has a graded Mo profile. Sheet resistance measurements on Mo incorporated CZTS films deposited on SLG and on quartz show resistivity that decreases with the amount of Mo in CZTS and Mo acts as an acceptor dopant. The energy band gap of CZTS on SLG increases from 1.38 eV to about 1.68 eV as a result of Mo incorporation and the absorbance of Mo incorporated CZTS is increased for wavelengths shorter than 600 nm. When Mo is co-deposited at the optimized DC sputtering power of 10 W, Mo incorporated CZTS/CdS solar cells attain a maximum power conversion efficiency (PCE) of 5.49% versus 1.63% for the reference device under 1 Sun AM 1.5 illumination. Device efficiency enhancement is due to back surface field, increased carrier concentration and reduced band tailing.